2003
DOI: 10.1203/01.pdr.0000059221.40073.82
|View full text |Cite
|
Sign up to set email alerts
|

Intracisternal Application of Endotoxin Enhances the Susceptibility to Subsequent Hypoxic-Ischemic Brain Damage in Neonatal Rats

Abstract: Perinatal brain damage is associated not only with hypoxicischemic insults but also with intrauterine inflammation. A combination of antenatal inflammation and asphyxia increases the risk of cerebral palsy Ͼ70 times. The aim of the present study was to determine the effect of intracisternal (i.c.) administration of endotoxin [lipopolysaccharides (LPS)] on subsequent hypoxic-ischemic brain damage in neonatal rats. Seven-day-old Wistar rats were subjected to i.c. application of NaCl or LPS (5 g/pup). One hour la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
32
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 39 publications
5
32
0
5
Order By: Relevance
“…inflammatory and apoptotic response could help to explain the primary sensitizing effect of LPS found in the immature brain in vivo (6,(21)(22)(23).We also found that LPS sensitized the immature brain if given 72 h before HI either at PND 4 or PND 7. This is interesting in that the animals have completely recovered from the systemic effects of LPS after 3 d. Early physiologic changes found after LPS injection, related to blood glucose, heart rate, temperature, and behavior, returned to normal after 3 d (24 -26).…”
supporting
confidence: 64%
“…inflammatory and apoptotic response could help to explain the primary sensitizing effect of LPS found in the immature brain in vivo (6,(21)(22)(23).We also found that LPS sensitized the immature brain if given 72 h before HI either at PND 4 or PND 7. This is interesting in that the animals have completely recovered from the systemic effects of LPS after 3 d. Early physiologic changes found after LPS injection, related to blood glucose, heart rate, temperature, and behavior, returned to normal after 3 d (24 -26).…”
supporting
confidence: 64%
“…[3][4][5] This synergistic effect was also reproduced in mammalian and avian animal models, combining HI insult and the lipopolysaccharide break-down product of bacteria in HI animal models. [6][7][8][9][10] However, the molecular mediators of this endotoxin effect in vivo are currently still unknown.…”
mentioning
confidence: 99%
“…There is a sensitization of the fetal brain to a subsequent hypoxic-ischemic insult after intraperitoneal or intracisternal application of bacterial endotoxins. 29,30 Here also, premyelinating oligodendrocyte injury takes place. In addition to a reduction in myelination, this leads to a secondary loss of small volumes of brain cortical and deep gray matter.…”
Section: Multiorgan Overviewmentioning
confidence: 99%